English as a foreign language: speech acts and greetings by saudi learners - Almegren, Rehan (UMA Editorial, 2017)
This study aims to explore the correlation between learners’ pragmatic competence performance and language proficiency. It further aims to determine the degree to which pragmatic shifts take place from L1 to L2 in relation to usage and interpretation of speech acts of greeting. The study focused on the identification of speech acts, especially by Saudi students of English as a Foreign Language, providing a comparison between the greeting strategies of intermediate– and advanced–level students, in order to determine pragmatic transfer in their responses. Based on research questions and hypotheses, a personal information survey together with a Discourse Completion Test (DCT) were conducted among female participants between 20–25 years old, comprising 200 respondents from four different groups: Saudi Arabic Speakers (SAS), American English Speakers (AES), Intermediate English Learners (IEL) and Advanced English Learners (AEL). Analysing the data collected from the stated sources, it was found that AEL and AES used a higher number of words compared to the native Arabic speakers and IEL. Moreover, all four groups were found to use strategies of greeting (oral speech, body language and other strategies) in different situations. It was also observed that pragmatic transfer was present in the AEL and IEL groups in some of the provided situations, which, furthermore, showed results somehow similar to those of the AES group. Finally, it could be concluded that AEL participants need a certain amount of socio–cultural understanding of the new strategies of greeting of the L2, in this case English, while IEL respondents also need to realise and understand them.
Keywords: Inglés - Estudio y enseñanza - Tesis doctorales; Lengua; Cultura; Inglés como lengua extranjera; Pragmática; Lingüística